Exploring the Influence of Gamification on Financial Behavior in Digital Financial Applications: A Systematic Literature Review - Aisyah Shabira Yavie; Intan Rizky Mutiaz (International Journal of Management Science and Information Technology, 2026)
This study aims to examine the role of gamification elements in influencing user behavior within digital financial applications and to identify which elements are most associated with the development of financial habits. This research adopts a Systematic Literature Review (SLR) approach guided by the PRISMA framework. Literature was collected from three academic databases, namely Scopus, ScienceDirect, and IEEE Xplore, covering publications between 2019 and 2025. After applying predefined inclusion and exclusion criteria, 17 empirical studies were selected and analyzed using thematic analysis. The findings indicate that gamification significantly enhances user engagement and financial behavior by making financial management activities more interactive and motivating. The most frequently implemented elements include points, rewards, badges, leaderboards, and progress tracking. Cash-based rewards show stronger effects in encouraging short-term transactional behaviors, while progress visualization and real-time feedback contribute to sustained financial management practices. This study contributes theoretically by synthesizing behavioral and technology adoption perspectives to explain how gamification mechanisms influence financial behavior in digital contexts. Practically, the findings offer insights for developers and financial institutions to design more effective and user-centered financial applications. However, this review has several limitations. Most included studies rely on self-reported survey data, which limits causal inference. In addition, the majority were conducted in emerging market contexts, which may constrain the generalizability of the findings. Furthermore, most studies focus on short-term behavioral outcomes, leaving long-term habit formation insufficiently explored. Future research is therefore needed to examine long-term effects and to investigate how cultural and socioeconomic factors influence the effectiveness of gamification.